2020
DOI: 10.1038/s41598-020-74479-x
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal squamous cell carcinoma: radiomic machine-learning classifiers from multiparametric MR images for determination of HPV infection status

Abstract: We investigated the ability of machine-learning classifiers on radiomics from pre-treatment multiparametric magnetic resonance imaging (MRI) to accurately predict human papillomavirus (HPV) status in patients with oropharyngeal squamous cell carcinoma (OPSCC). This retrospective study collected data of 60 patients (48 HPV-positive and 12 HPV-negative) with newly diagnosed histopathologically proved OPSCC, who underwent head and neck MRIs consisting of axial T1WI, T2WI, CE-T1WI, and apparent diffusion coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 45 publications
1
21
1
Order By: Relevance
“…To overcome this limitation, we analyzed the results using 20 repeated 10-fold strati ed cross-validation. This method, as shown in previous studies [32][33][34][35], was the best way to increase the reliability of the evaluation using limited data. Third, external validation for machine learning was not performed, limiting the generalizability of our results.…”
Section: Discussionmentioning
confidence: 83%
“…To overcome this limitation, we analyzed the results using 20 repeated 10-fold strati ed cross-validation. This method, as shown in previous studies [32][33][34][35], was the best way to increase the reliability of the evaluation using limited data. Third, external validation for machine learning was not performed, limiting the generalizability of our results.…”
Section: Discussionmentioning
confidence: 83%
“…No researcher registered a prospective study in a trial database or performed a cost-effectiveness analysis, but 4 investigators did share the data obtained. Elhalawani shared the dataset generated for the study in Figshare repository [ 22 ], other authors share the code [ 23 , 24 ], while Suh shared the datasets and the analysis on reasonable request [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The resulting relevant radiomic features extracted from CT images have shown potential for HPV status prediction either in internal [ 8 , 35 38 ] or external validation [ 39 ]. Other authors employed T1-weighted post contrast [ 25 , 40 , 41 ] and ADC [ 25 , 42 ] images on MRI, and a combination of PET-based and CT-based radiomics on PET/CT [ 23 ]. In some cases, specific steps within the radiomic pipeline were also explored, such as comparison between 2 and 3D segmentation [ 43 ] and variations due to different CT scanners [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that using random forest as a feature selector and classifier resulted in the highest prognostic performance. In another study, Suh et al 57 compared the predictive performance of different algorithms, including logistic regression, random forest, and XGboost for human papillomavirus status classification using MRI radiomic features. They reported that logistic regression and random forest provided the highest accuracy.…”
Section: Discussionmentioning
confidence: 99%